2021
DOI: 10.1002/ijch.202100103
|View full text |Cite
|
Sign up to set email alerts
|

Glycine: The Gift that Keeps on Giving

Abstract: Glycine is a small molecule. It cannot change its conformation and is achiral. Despite the apparent simplicity, glycine shows endless diversity in its behavior over many phenomena. It was the first amino acid for which polymorphism was reported, first on crystallization and then on hydrostatic compression. The polymorphs differ in their physical properties and their biological activity. Glycine clusters persist in solution, leading to "solution memory". Phenomena at interfaces are critically important for crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 341 publications
(460 reference statements)
1
15
0
Order By: Relevance
“…Complex 2) to all data points; the dashed line is a fit to the first five data points above the transition at 100 K (compare Table III). (d) Normalized lattice parameters a/a 0 with a 0,6 K = 3.7650(4) and a 0,100 K = 3.7645( 1 superstructures at high pressures have been established in other systems too [55][56][57]. It is the general expectation that compounds attain simple packings at the highest pressures [56].…”
Section: A High-pressure-low-temperature Phase Diagrammentioning
confidence: 96%
“…Complex 2) to all data points; the dashed line is a fit to the first five data points above the transition at 100 K (compare Table III). (d) Normalized lattice parameters a/a 0 with a 0,6 K = 3.7650(4) and a 0,100 K = 3.7645( 1 superstructures at high pressures have been established in other systems too [55][56][57]. It is the general expectation that compounds attain simple packings at the highest pressures [56].…”
Section: A High-pressure-low-temperature Phase Diagrammentioning
confidence: 96%
“…On a completely different scale, glycine has been found in the interstellar medium (Kuan et al, 2003;Ioppolo et al, 2021) and in the comas of comets and meteorites, (Elsila et al, 2009;Altwegg et al, 2016) thus providing evidence of the panspermia hypothesis (Wesson, 2010). As for the functional physical properties of crystalline glycine, they largely depend on the supramolecular packing of its molecules into three main polymorphs (α, β, and γ), resulting in different crystallographic structures (Heredia et al, 2012;Guerin et al, 2017;Gleeson et al, 2020;Boldyreva, 2021). It has been a long time established that the α-phase is centrosymmetric (space group P2 1 /n), in which only surface piezoelectricity and pyroelectricity may exist via doping or water incorporation (Piperno et al, 2013;Meirzadeh et al, 2018;Dishon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That work attracted a wide interest of the research community in different fields and has launched a new round of experimental and theoretical studies of glycine (Bystrov et al, 2014;Bystrov et al, 2015;Bystrov et al, 2016;Guerin et al, 2017;Seyedhosseini et al, 2017;Bai et al, 2018;Tasnim et al, 2018;Hu et al, 2019;Slabov et al, 2019;Bishara et al, 2020;Dishon et al, 2020;Gleeson et al, 2020;Hosseini et al, 2020;Kholkin et al, 2021). Several reviews reported piezoelectric properties of glycine (Tayi et al, 2015;Tofail and Bauer, 2016;Guerin et al, 2017;Maiti et al, 2019;Kim et al, 2020;Li et al, 2020;Boldyreva, 2021;Xu et al, 2021). However, until now, its ferroelectric properties have not been summarized and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…We first showed that the nonmonotonic behavior could not be rationalized by considering the molecular attachment to a nucleus directly from the solution. In fact, glycine is also known to form stable intermediary structures in solution ,,, supposed to be precursors of the nucleation . Thus, we investigated the shear-induced coalescence rate of the intermediary structures under sheared conditions until reaching a critical size at which the phase change takes place.…”
Section: Discussionmentioning
confidence: 99%